2015
DOI: 10.1186/s12889-015-2478-7
|View full text |Cite
|
Sign up to set email alerts
|

Positive strategies men regularly use to prevent and manage depression: a national survey of Australian men

Abstract: BackgroundMen are at greater risk than women of dying by suicide. One in eight will experience depression – a leading contributor to suicide – in their lifetime and men often delay seeking treatment. Previous research has focused on men’s use of unhelpful coping strategies, with little emphasis on men’s productive responses. The present study examines the positive strategies men use to prevent and manage depression.MethodA national online survey investigated Australian men’s use of positive strategies, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…For this study, access to the existing 12 myCompass modules was restricted to ensure users’ engagement with the new module (Man Central) only (see Figure 1 ). Man Central was developed for men with depression, based on the results from two previous phases of research exploring men’s use of and preferred positive strategies to prevent and manage symptoms of depression, including suicidal ideation [ 36 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…For this study, access to the existing 12 myCompass modules was restricted to ensure users’ engagement with the new module (Man Central) only (see Figure 1 ). Man Central was developed for men with depression, based on the results from two previous phases of research exploring men’s use of and preferred positive strategies to prevent and manage symptoms of depression, including suicidal ideation [ 36 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Given the increasing rates of mental health issues in men, the lack of published studies examining the role of behaviour change programs to treat men with current mental health conditions (eg, depression or anxiety) is an important limitation to address in future research. Indeed, observational research suggests that men with mental health concerns often report using lifestyle behaviour change as a way of managing their condition . For example, in a recent study of men with depression, Proudfoot and colleagues reported that exercise and eating healthy were two of the top five prevention strategies men used regularly to deal with their symptoms .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, observational research suggests that men with mental health concerns often report using lifestyle behaviour change as a way of managing their condition . For example, in a recent study of men with depression, Proudfoot and colleagues reported that exercise and eating healthy were two of the top five prevention strategies men used regularly to deal with their symptoms . Further, behaviour change programs may be particularly appealing for men who align to traditional forms of masculinity, as studies suggest they are less likely to seek help for psychological concerns because of socialized negative beliefs associated with traditional mental health treatments .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations